Hubungan Stigma Diri Dan Lama Pengobatan Dengan Tingkat Stres Pada Pasien TB Paru Di RS Bhakti Asih Brebes - Mohammad Taufik Akbar; Dwi Retno Sulistyaningsih; Indah Sri Wahyuningsih (STIKes Ibnu Sina Ajibarang, 2025)
Tuberculosis (TB) remains a global health problem. It was the second leading cause of death worldwide after COVID-19 in 2022. More than 10 million people contract TB each year. Pulmonary TB patients are often shunned by society due to fear of contagion, which creates a negative stigma. Stress is the body's response to demands that exceed its ability to cope with and resolve problems. This study aimed to determine the relationship between self-stigma and duration of TB treatment with stress levels in pulmonary TB patients at Bhakti Asih Brebes Hospital. This quantitative study used a correlational analysis method with a cross-sectional approach. The sample consisted of 55 TB patients using a total sampling technique. Self-stigma was measured using Van Rie's TB Stigma Scale (VTSS) and stress levels were measured using the Perceived Stress Scale (PSS). The analysis was performed using the Spearman Rank test. There was a relationship between self-stigma (0.0001) and duration of treatment (0.028) with stress levels in pulmonary TB patients. The better the patient's self-stigma, the lower the stress experienced, while the longer the treatment, the lower the stress experienced.